2017
DOI: 10.1177/0091415017720888
|View full text |Cite
|
Sign up to set email alerts
|

Felt Age, Desired, and Expected Lifetime in the Context of Health, Well-Being, and Successful Aging

Abstract: This study examines the interrelations of three different aspects of the subjective age: felt, desired and expected, as well as their relations with the chronological age (CA), health, and psychological well-being variables. Four hundred and twenty-three community-dwelling Croatian adults, aged 60-95 years, participated in the study. All three subjective age measures significantly correlated with the CA. Self-rated health were better predictors of the subjective age compared to the psychological variables. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
(69 reference statements)
2
18
0
Order By: Relevance
“…Overall, our findings on correlates of and reasons for felt age are in line with those of previous studies with respect to the biopsychosocial and behavioral contributors to felt age identity among older adults (Ambrosi-Randić et al, 2018; Shinan-Altman & Werner, 2019). Our findings also underscore the importance of supportive and enabling environments as potentially significant contributors to younger felt age and positive attitudes toward aging among these racial/ethnic minority older adults of lower socioeconomic status.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, our findings on correlates of and reasons for felt age are in line with those of previous studies with respect to the biopsychosocial and behavioral contributors to felt age identity among older adults (Ambrosi-Randić et al, 2018; Shinan-Altman & Werner, 2019). Our findings also underscore the importance of supportive and enabling environments as potentially significant contributors to younger felt age and positive attitudes toward aging among these racial/ethnic minority older adults of lower socioeconomic status.…”
Section: Discussionsupporting
confidence: 91%
“…Research shows that felt age identity or how old one feels is a strong predictor of physical and mental health outcomes, including morbidity, hospitalization, mortality, depressive symptoms, and overall life satisfaction, over and above chronological age (Choi & DiNitto, 2014; Christensen et al, 2009; Gunn et al, 2016; Mock & Eibach, 2011; Stephan et al, 2011, 2013; Uotinen et al, 2005). Research also shows that objective physical/functional health conditions and self-perceptions of health explain the largest proportions of variance in felt age, with poorer health contributing to feeling older (Ambrosi-Randić et al, 2018; Barrett, 2003; Bergland et al, 2014; Demakakos et al, 2007; Hubley & Russell, 2009). Felt age is also associated with psychological health factors such as self-efficacy, internal locus of control, optimism, extraversion, and openness (Bellingtier & Neupert, 2020; Canada et al, 2013; Hubley & Hultsch, 1994; Teuscher, 2009); depressive symptoms (Choi & DiNitto, 2014); positive/negative affect and life satisfaction (Dutt & Wahl, 2017; Kotter-Grühn et al, 2015); and memory self-efficacy and cognitive test scores (e.g., word-list memory recall; Ihira et al, 2015; Stephan et al, 2011).…”
mentioning
confidence: 96%
“…One potential reason for such low longevity desires might be the wish to avoid old age as a phase of heightened vulnerability and health declines. Most participants (86.0%) however wished for a life span ranging from 71 to 119 years, with a mean desired longevity of M = 88.9 years ( SD = 8.3) which is comparable to prior studies (e.g., Ambrosi-Randic et al, 2018; Lang et al, 2007). However, 14 participants gave illogical, and invalid responses (i.e., lower than current chronological age), and had to be excluded from the analysis.…”
Section: A Pilot Study and Empirical Illustrationsupporting
confidence: 69%
“…The largely separate development of the two literature bodies implies that data on SA and SLE are not often combined in one study, and empirical evidence on which of them shows stronger associations with health leans on only a few studies. Among the three pertinent studies we could find, two were set in Israel and one in Croatia, and all were cross-sectional and included community-living samples aged 50 years and over ( Ambrosi-Randić et al, 2018 ; Palgi, 2016 ; Shrira et al, 2014 ). The Croatian study showed similar predictive values for SA and SLE of self-rated physical (betas .26 and .21, respectively) and mental health (both betas .16).…”
Section: Introductionmentioning
confidence: 99%